Investment Constraints in Urban Regeneration: Property Developers and Local Authorities Perspective - Mohamed Nurulanis Ahmad; Baharum Zarita Ahmad; Senawi Asma; Salleh Nor Aini (MATEC Web of Conferences, 2016)
Urban decay is a phenomenon created due to the expansion of urban population, the restructuring of industrial, social composition as well as the deterioration of urban areas. Consequently this will increase issues of crime, mass unemployment, low quality in urban services, social problems etc. Thus urban regeneration is a tool used to overcome all these issues in order to create quality of urban living, diversify and vibrant cities. However, the involvement of investment in urban regeneration is still infancy in Malaysia as compared to other countries such as Australia, UK, Hong Kong, and etc. This is due to the perception of investors towards the profit generation and the risk involve. The objective of this paper is to determine the constraints involved in urban regeneration investment from the perspectives of the property developer companies and the local authorities. The method used is an exploratory with primary data collection through a questionnaire survey. The findings revealed that the main constraints is in regards of the land issues as well as high cost of investment, however, the benefits gain should also be considered as this create a livable urban living.